2017
DOI: 10.24953/turkjped.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of socioeconomic status on allergic diseases and atopy in school children

Abstract: Sipahi S, Nacaroğlu HT, Can D, Günay İ, Ünsal-Karkıner CŞ, Kamalı H, Özdemir A, Günay T. Effect of socioeconomic status on allergic diseases and atopy in school children. Turk J Pediatr 2017; 59: 670-677. Higher family socioeconomic status (SES) has been suggested as a risk factor for allergic diseases. We investigated the effect of SES on the prevalence of allergic diseases and atopy. The study included 13-14-year-old primary school students in Kemalpaşa, Turkey. The International Study of Asthma and Allergie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With the objective to document EDN levels, the slightly higher education level and proportion of allergic diseases among the parents in the PreventADALL cohort than in the general population 24 limit the generalizability of our observations to similar populations, as disease burden, 38 and thereby likely EDN levels, may differ with socioeconomic status. Children sensitized to allergens such as tree nuts will not have been identified at 3 years, but the potential impact on observed associations is likely to be small.…”
Section: Discussionmentioning
confidence: 99%
“…With the objective to document EDN levels, the slightly higher education level and proportion of allergic diseases among the parents in the PreventADALL cohort than in the general population 24 limit the generalizability of our observations to similar populations, as disease burden, 38 and thereby likely EDN levels, may differ with socioeconomic status. Children sensitized to allergens such as tree nuts will not have been identified at 3 years, but the potential impact on observed associations is likely to be small.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the socioeconomic status of an individual, which affects their burden of spending on such care services, was identified as a specific factor contributing to the poor utilization of healthcare services. Numerous studies have reported that SES is associated with healthcare utilization according to parental education and household income [9,12,17,18,24,27]. Another study reported that the burden of medical expenses for preschool children is lower than in other nations due to universal medical insurance and regional government subsidies for children's medical expenses [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, hospital utilization is higher in urban than rural areas, and hospitals in rural areas typically have less resources than the facilities in urban areas. Furthermore, since the health disparities related to the association between gender and age have already been studied in children [11][12][13][14][15][16][17][18], there is a need for research on the health disparities related to the association between SES and healthcare utilization. This study assumed that healthcare utilization might vary depending on SES categories.…”
Section: Introductionmentioning
confidence: 99%
“…16 Potential confounding variables were proposed based on the existing literature on air pollution and/or allergic sensitisation or diseases. [23][24][25][26][27][28][29][30] Two minimal su cient adjustment sets of confounders were identi ed based on a directed acyclic graph (DAG) using DAGitty v3.0 (Figure S1). 31 The rst one, selected for our primary analysis, included three variables: maternal education (≤ year 12 vs. > year 12), child age in months at the time of the blood collection, and Index of Relative Socio-economic Disadvantage (IRSD) decile of the household.…”
Section: Covariatesmentioning
confidence: 99%